Procurement Practices and Operation Efficiency in State-Owned Enterprises: A Case of Eskom Holdings Ltd and Airports Company South Africa Ltd - Manyathi, Sakhile; Jarbandhan, Vain (African Journal of Governance and Development, 2024)
Governments around the world establish state-owned enterprises (SoEs) to drive revenue generation and promote socioeconomic development. In South Africa, SoEs face significant challenges in balancing service delivery mandates, economic objectives, and compliance with public procurement legislation. This highlights the critical role of effective procurement practices in fostering transparency, fairness, and efficiency. This investigation focused on procurement practices at Eskom Holdings Ltd (Eskom) and the Airports Company South Africa Ltd (ACSA), two key SoEs in South Africa. The study aimed to analyse and identify procurement processes that could enhance operational efficiency and effectiveness in both organisations. A purposive sampling strategy was employed to select fifteen participants from strategic business areas within Eskom and ACSA. The research used thematic analysis, a qualitative approach, to uncover critical insights. Findings revealed that although Eskom and ACSA both prioritise transparency, fairness, and compliance, Eskom places greater emphasis on cost competitiveness, sometimes at the expense of strict adherence to procurement legislation. Moreover, political interference emerged as a major factor undermining decision-making processes, reducing transparency and operational efficiency across both entities. This study contributes to the body of knowledge by synthesising current research, addressing gaps, and providing actionable recommendations for improving procurement practices at Eskom and ACSA to better align with governance principles and legislative requirements.